Microdebrider assisted turbinoplasty for nasal obstruction in inferior turbinate hypertrophy: a systematic review and meta-analysis - Kanesan, Nithya (2020)
Introduction: Common cause of nasal obstruction is inferior turbinate hypertrophy and microdebrider is a new method for inferior turbinoplasty that preserves mucosa. Objective(s): The objective of this study is to examine the efficacy of microdebrider assisted inferior turbinoplasty compared to other standard techniques. Our primary outcome is to assess the relieve in nasal obstruction. Our secondary objective is to assess the relieve of other nasal symptoms and complications related to these techniques. Methods: We retrieved trials from the Cochrane Register of Controlled Trials CENTRAL which includes MEDLINE. We used Review Manager 5.3.5 software to perform the meta-analysis. Results: We retrieved 124 records from the search of the electronic database and other sources. 11 trials were included systematic review and 10 studies in meta-analysis. There is a reduction in nasal obstruction in the microdebrider group when compared to radiofrequency (SMD -0.58, 95% CI -1.01 to -0.15; P=0.008, I2=76%; 4 studies, 400 patients). However, there is no difference when compared between the microdebrider and submucosal resection (MD -0.10, 95% CI -0.36 to 0.15; P=0.13, I2=57%; 2 studies, 280 patients). There is no difference between microdebrider and radiofrequency or submucosal resection in reduction of other nasal symptoms. Hemorrhage is increased in the microdebrider group when compared to radiofrequency but no difference when compared with submucosal resection. However, crusting was noted to be less in the microdebrider group when compared with submucosal resection group. Conclusion(s): Microdebrider offers an alternative, safe method for inferior turbinoplasty. However, the efficacy of the microdebrider is unsure until new trials are available to make a further recommendation.